Tinjauan Yuridis Ketetapan Mpr Tentang Pelantikan Presiden Wakil Presiden - Putri, S A P Chandra Kusumaning; Harvelian, Agnes (HUMANIORUM, 2025)
The Decree of the People's Consultative Assembly (MPR) regarding the inauguration of the President and Vice President in Indonesia plays a crucial role in determining the validity and legitimacy of the elected leaders. This decree serves as the legal foundation that regulates the entire inauguration process, ensuring that each step is carried out in accordance with applicable regulations, thereby providing legal guarantees to the public. The MPR, as the supervisory body, has the responsibility to maintain transparency and accountability during the inauguration, which in turn strengthens public trust in the democratic system. However, challenges in interpreting and implementing this decree still exist. Therefore, it is essential to ensure that all parties understand and respect the established provisions. This includes a clear understanding of the proceduresoutlined in the amendments to the MPR's Rules of Procedure. Thus, the implementation of this decree is a commitment to a strong democratic principles in Indonesia.